Domestic food practices: A study of food management behaviors and the role of food preparation planning in reducing waste - Romani, Simona; Grappi, Silvia; Bagozzi, Richard P.; Barone, Ada Maria (Appetite, 2018)
Recent research has started to show the key role of daily food provision practices in affecting household food waste. Building on and extending these previous contributions, the objective of this paper is to investigate how individuals' everyday practices regarding food (e.g., shopping, cooking, eating, etc.) lead to food waste, and how policy makers and the food industry can implement effective strategies to influence such practices and ultimately help consumers reduce food waste. The research performs three Studies; a critical incident qualitative study (Study 1; N = 514) and a quantitative, survey-based study (Study 2; N = 456) to identify and examine relevant food management behaviors associated with domestic waste. Lastly, findings from a field experiment (Study 3; N = 210) suggest that a specific educational intervention, directed at increasing consumers' perceived skills related to food preparation planning behaviors, reduces domestic food waste. Implications of the research for policy makers and the food industry are discussed.